2015
DOI: 10.1021/acs.chemmater.5b00072
|View full text |Cite
|
Sign up to set email alerts
|

A Crystal-Chemical Framework for Relaxor versus Normal Ferroelectric Behavior in Tetragonal Tungsten Bronzes

Abstract: Tetragonal tungsten bronzes (TTBs), an important class of oxides known to exhibit ferroelectricity, undergo complex distortions, including rotations of oxygen octahedra, which give rise to either incommensurately or commensurately modulated superstructures. Many TTBs display broad, frequency-dependent relaxor dielectric behavior rather than sharper frequency-independent normal ferroelectric anomalies, but the exact reasons that favor a particular type of dielectric response for a given composition remain uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
166
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(181 citation statements)
references
References 50 publications
(189 reference statements)
13
166
1
1
Order By: Relevance
“…It is important to note that Chen and co-workers also proposed a model to predict relaxor vs. ferroelectric behavior but which considered only the difference in A-site cation radii. 37,39 As part of the proposed crystal-chemical framework 20 and in earlier 40 studies we reported the properties of a family of "empty" TTBs of general formula TTBs Ba 4 R 0.67…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…It is important to note that Chen and co-workers also proposed a model to predict relaxor vs. ferroelectric behavior but which considered only the difference in A-site cation radii. 37,39 As part of the proposed crystal-chemical framework 20 and in earlier 40 studies we reported the properties of a family of "empty" TTBs of general formula TTBs Ba 4 R 0.67…”
mentioning
confidence: 89%
“…19 The origins of these superstructures are principally variations in the oxygen positions due to octahedral tilting out of the ab plane. [20][21][22][23][24][25][26][27][28][29][30] . When these variations are periodic, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The tetragonal tungsten bronze structure is composed of ten distorted octahedral sharing corners in such a way that three different interstices (2 tetragonal A1, 4 pentagonal A2, and 4 triangle C) are available for cations in the general formula (A1) 2 (A2) 4 (C) 4 (B1) 2 (B2) 8 O 30 28 . In recent years, a number of Pb-free ferroelectrics with tetragonal tungsten bronze structures have been determined [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] 39,40 . A detailed structural study indicated that the relaxor nature is always associated with incommensurate superlattice modulation.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed structural study indicated that the relaxor nature is always associated with incommensurate superlattice modulation. The decrease in the R cation size increases the driving force for commensurate superlattice modulation, which dominates the normal ferroelectric nature [29][30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…456 A recent framework for frustrated ferroelectricity in tetragonal tungsten bronzes was developed based on competing instabilities. 464 This suggests that a proper understanding of structural instabilities and associated order parameters, as well as their couplings, is mandatory in order to engineer the functionality of several classes of advanced ceramics. Ferroelectrics have been traditionally designed around FD phase instabilities 169 to maximize strain output such as was treated for BZT-BCT (Section 5.1).…”
Section: Discussionmentioning
confidence: 99%